2009
DOI: 10.1111/j.1476-5829.2009.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant feline interferon‐ω alone and in combination with chemotherapeutic agents on putative tumour‐initiating cells and daughter cells derived from canine and feline mammary tumours

Abstract: Interferons (IFNs) are naturally produced cytokines with multiple important biological functions. The activity of recombinant feline IFN-omega (rFeIFN-omega) alone and in combination with chemotherapeutic drugs was tested on canine and feline mammary carcinoma cell lines (REM134 and CAT-MT) and putative tumour-initiating cells (TIC) derived from these cell lines by sphere assay. Viability was measured by chemoluminescence and a one-way analysis of variance and Student's t-tests were used for statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…For example, the effect of recombinant feline interferon-omega, alone or in combination with anthracycline chemotherapeutic drugs, was evaluated using CSC derived from the carcinoma cell lines REM134 and CAT-MT. Hereby, it was found that the CSC were more resistant to the actions of interferon-omega than the REM134 and CAT-MT cell lines [75]. A similar result was found with the chemotherapeutic drug doxorubicin, where spheres derived from the canine adenocarcinoma cell line CHMp and REM134 had chemoresistant characteristics [72,73].…”
Section: Figsupporting
confidence: 65%
See 1 more Smart Citation
“…For example, the effect of recombinant feline interferon-omega, alone or in combination with anthracycline chemotherapeutic drugs, was evaluated using CSC derived from the carcinoma cell lines REM134 and CAT-MT. Hereby, it was found that the CSC were more resistant to the actions of interferon-omega than the REM134 and CAT-MT cell lines [75]. A similar result was found with the chemotherapeutic drug doxorubicin, where spheres derived from the canine adenocarcinoma cell line CHMp and REM134 had chemoresistant characteristics [72,73].…”
Section: Figsupporting
confidence: 65%
“…The first description on the isolation of feline CSC came from the research group of Argyle, where they derived putative CSC from the feline mammary carcinoma (FMC) cell line CAT-MT [75]. Later on, another group also characterized CSC from FMC.…”
Section: Figmentioning
confidence: 99%
“…These data may suggest a higher doxorubicin resistance of TiHo-0906 cells to that reported in an FMC cell line 78 . Nonetheless, methodological differences in viability assessment and exposure time to doxorubicin make comparison difficult.…”
Section: Discussionmentioning
confidence: 60%
“…In vitro culture models are pivotal to understanding the role of EMT in the oncogenic process of FMC, determining the presence of possible subtypes and developing of new therapeutic approaches. However, the number of established FMC cell lines is still small 30,39,75–78,81–83 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in human medicine have proposed a novel strategy for the treatment of cancer targeted at CSCs, and notable results have been presented regarding CSCs from basic and clinical trials (28). Veterinary medicine follows human medicine, and CSCs have been reported from various types of solid tumor and hematological malignancies (29)(30)(31)(32). To the best of our knowledge, the current study is the first to describe CSCs identified by rhodamine in a canine cancer cell line, and it may lead to basic studies regarding cHCSC-targeting treatment.…”
Section: Discussionmentioning
confidence: 99%